2015
DOI: 10.4236/ojanes.2015.57025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dexmedetomidine on Oxygenation and Intrapulmonary Shunt during One Lung Ventilation

Abstract: Background: The effect of intravenously administered dexmedetomidine on oxygenation during one-lung ventilation has not been studied. The hypothesis of this prospective, randomized study was that dexmedetomidine would be associated with an improvement in oxygenation during onelung ventilation. The secondary outcome was the change in the intrapulmonary shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…In the present study, there was no significant difference in the demographic data of the patients and improvement was demonstrated in oxygenation during OLV in the DISO group. The results from the Buget et al study indicated that demographic data and baseline characteristics were not statistically significant and also dexmedetomidine infusion improved oxygenation and lung mechanics in patients with restrictive lung disease (14). These findings are in line with our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, there was no significant difference in the demographic data of the patients and improvement was demonstrated in oxygenation during OLV in the DISO group. The results from the Buget et al study indicated that demographic data and baseline characteristics were not statistically significant and also dexmedetomidine infusion improved oxygenation and lung mechanics in patients with restrictive lung disease (14). These findings are in line with our study.…”
Section: Discussionsupporting
confidence: 90%
“…Hypoxia during OLV is considered as an important concern throughout thoracic anesthesia. Hypoxic pulmonary vasoconstriction is a defense mechanism against hypoxia reducing the shunt (14,15). In the present study, there was no significant difference in the demographic data of the patients and improvement was demonstrated in oxygenation during OLV in the DISO group.…”
Section: Discussioncontrasting
confidence: 51%
“…This phenomenon indicates that isoflurane may increase intrapulmonary shunt and reduce the systematic oxygenation. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lack of inhibitory effects on HPV is of great importance in anesthetizing those undergoing OLV [4,5]. It is a defense mechanism against hypoxia that reduces pulmonary stenosis [6,7].…”
Section: Introductionmentioning
confidence: 99%